Polyimide modified COFs, preparation method thereof, polyimide modified COFs membrane and application

Through the preparation method of polyimide modified COFs, the "Trade-off" effect of the mixed matrix membrane with polymer-based film doped nanoparticles in terms of gas permeability and selectivity is solved, and efficient gas selective separation performance is achieved.

CN119899375APending Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311412049.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, the mixed matrix membrane doped with polymer-based films has a "Trade-off" effect in terms of gas permeability and selectivity, making it difficult to simultaneously improve the gas separation performance.

Method used

By using polyimide-modified COFs preparation method, including preparing COFs powder and polymerizing with diamine monomer and dianhydride monomer, forming a polyimide-modified COFs film, the problem of poor agglomeration and compatibility of nanoparticles in the base film is solved and the gas separation performance of the film is improved.

Benefits of technology

The stable performance of the polyimide-modified COFs film in gas selective separation is achieved, the crack problem of the film is avoided, and the CO2 permeability coefficient and CO2/N2 separation selectivity is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899375A_ABST
    Figure CN119899375A_ABST
Patent Text Reader

Abstract

The invention relates to the field of gas separation membranes, in particular to polyimide modified COFs, a preparation method of the polyimide modified COFs, a polyimide modified COFs membrane and application of the polyimide modified COFs membrane. The preparation method of the polyimide modified COFs comprises the following steps that S1, COFs powder is prepared; s2, the COFs powder, a diamine monomer and a dianhydride monomer are subjected to a polymerization reaction, and the polyimide modified COFs are obtained. According to the specific preparation method, the polyimide is adopted to modify the COFs, and modification of the polyimide on the specific COFs is achieved; moreover, the membrane prepared from the polyimide modified COFs can exist stably, gas can selectively pass through the membrane, the membrane is used for separating gas with different sizes, and selective separation of the gas is successfully realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of gas separation membranes, and in particular to polyimide-modified COFs and a preparation method thereof, a polyimide-modified COFs membrane and applications. Background Art

[0002] Compared with traditional chemical adsorption and physical adsorption methods, membrane separation technology has the advantages of low energy consumption, high stability, environmental friendliness, and easy operation, and is considered to be one of the most promising methods for CO2 capture and storage (CCS). Among them, the performance of the separation membrane is one of the main factors affecting whether the membrane separation technology can be applied on a large scale. The ideal separation membrane needs to have good chemical stability, thermal stability, mechanical stability, high CO2 permeability and selectivity.

[0003] Polymer membrane materials have the characteristics of good film-forming properties, easy large-scale production, and easy packaging. Therefore, polymer membranes have been widely used in the separation and capture of CO2 since they were first used to decarbonize natural gas in 2001. At present, the most studied polymer membrane material is polyimide, which has good thermal stability, chemical stability, mechanical stability, good CO2 permeability and selectivity, and reasonable preparation cost. However, there is a "trade-off" effect between the permeability and selectivity of polyimide membranes, especially linear polyimide membrane materials, and the separation performance is difficult to break through the Robertson upper limit. Doping inorganic / organic nanoparticles in polymer-based membranes to prepare mixed matrix membranes (MMMs) is an effective method to overcome the "trade-off" effect, in which the intrinsic properties of nanoparticles are one of the factors that ultimately affect the performance of mixed matrix membranes. At present, nanomaterials such as zeolite molecular sieves, metal organic framework compounds, carbon nanotubes, carbon molecular sieves, and graphene have been proven to effectively improve the gas separation performance of polyimide membranes.

[0004] The compatibility between the polymer matrix and the nanoparticle filler is poor, the nanoparticles have agglomeration problems in the base membrane, and the mixed matrix membrane is prone to form interface defects, which affects the performance of the membrane. Summary of the invention

[0005] The purpose of the present invention is to overcome the difficulties in organically modifying COFs in the prior art and the low gas permeability and selectivity of mixed matrix membranes, and to provide a polyimide-modified COFs and a preparation method thereof, a polyimide-modified COFs membrane and application.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing polyimide-modified COFs, wherein the preparation method comprises the following steps:

[0007] S1: Preparation of COFs powder;

[0008] S2: subjecting the COFs powder, diamine monomer and dianhydride monomer to a polymerization reaction to obtain polyimide-modified COFs.

[0009] The second aspect of the present invention provides polyimide-modified COFs prepared by the above-mentioned preparation method.

[0010] The third aspect of the present invention provides a polyimide-modified COFs film, wherein the polyimide-modified COFs film is obtained by film-forming the aforementioned polyimide-modified COFs.

[0011] A fourth aspect of the present invention provides an application of the aforementioned polyimide-modified COFs membrane in the field of gas separation.

[0012] Through the above technical solution, the beneficial effects of the invention are as follows:

[0013] In the specific preparation method of the present invention, polyimide is used to modify COFs, thereby realizing the modification of specific COFs by polyimide; and the membrane prepared by the polyimide-modified COFs can exist stably without cracking, can selectively pass gas, and is used to separate gases of different sizes, thereby successfully realizing selective gas separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is an electron microscope image of PI-COFs-1# of Example 1;

[0015] Figure 2 This is the XRD spectrum of PI-COFs-1# of Example 1. DETAILED DESCRIPTION

[0016] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0017] The first aspect of the present invention provides a method for preparing polyimide-modified COFs, wherein the preparation method comprises the following steps:

[0018] S1: Preparation of COFs powder;

[0019] S2: subjecting the COFs powder, diamine monomer and dianhydride monomer to a polymerization reaction to obtain polyimide-modified COFs.

[0020] In the present invention, polyimide is used to modify COFs to obtain polyimide-modified COFs. The morphology of the modified COFs can be observed through an electron microscope, and the surface changes from the original smooth and continuous state to a wrinkled surface.

[0021] In the present invention, in S1, the preparation method of COFs powder is the prior art in the art. In a particularly preferred embodiment, 20 mL of n-butanol (BuOH), 20 mL of o-dichlorobenzene (o-DCB), 3.2 mmol of 1,3,5-tris(4-aminophenyl)benzene (TPB) and 4.8 mmol of 2,5-bis(2-methoxyethoxy)terephthalaldehyde (BMTP) are added to a 500 mL ampoule tube, ultrasonicated for 5 min, and then 4 mL of 6 mol / L acetic acid aqueous solution is added; after the ampoule tube is vacuumed, it is placed in a constant temperature oven at 120°C, reacted at 120°C for 72 hours, and after the reaction is completed, centrifuged to obtain COFs powder, and then the powder is washed with tetrahydrofuran, repeated 3 times, and the solid powder is placed in a vacuum oven at 120°C and dried for 12 hours to obtain dry COFs powder.

[0022] In the present invention, in S2, a mixed solution of acetic anhydride and pyridine may be added during the polymerization reaction to carry out dehydration treatment to promote the continuous polymerization reaction.

[0023] In a particularly preferred embodiment, the molar ratio of the diamine monomer to the acetic anhydride in the mixed solution of acetic anhydride and pyridine is 1:2.4-4.8, preferably 1:3.2-3.6.

[0024] In a particularly preferred embodiment, in the mixed solution of acetic anhydride and pyridine, the molar ratio of acetic anhydride to pyridine is 1:0.8-1.2, preferably 1:1-1.1.

[0025] In a particularly preferred embodiment, the conditions for the dehydration treatment include: the dehydration temperature is 0-50°C, preferably 10-30°C, and the dehydration time is 18-36h, preferably 24-28h.

[0026] The method for treating polyimide-modified COFs after the polymerization reaction is a common treatment method in the art. In a particularly preferred embodiment, the dehydrated solution is poured into excess deionized water at 25°C, filtered, and boiled at 60°C, and repeated 3 times to obtain polyimide-modified COFs.

[0027] According to the present invention, in S2, the diamine monomer I is selected from

[0028] At least one of, preferably selected from At least one of

[0029] in, is 4,4'-diaminodiphenyl ether (4,4'-ODA), is 3,4'-diaminodiphenyl ether (3,4'-ODA), is 2,2-bis(trifluoromethyl)-4,4-diaminophenyl ether (6FODA), It is 4,4'-(1,3-phenylenedioxy)diphenylamine.

[0030] According to the present invention, the dianhydride monomer I is selected from

[0031] At least one of and / or More preferably

[0033] in, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA), It is 4,4'-phenylenedioxydiphthalic anhydride (HQDA).

[0034] According to the present invention, in S2, the weight ratio of the COFs powder, the diamine monomer and the dianhydride monomer is 0.01-10:0.5-1.2:1, preferably 0.1-5:0.6-1.1:1.

[0035] According to the present invention, in S2, the polymerization reaction is carried out in a solution.

[0036] According to the present invention, the solvent contained in the solution is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide, preferably N-methylpyrrolidone.

[0037] According to the present invention, the mass volume concentration of the COFs powder in the solvent is 0.005-0.1 g / mL, preferably 0.01-0.05 g / mL.

[0038] According to the present invention, in S2, the conditions of the polymerization reaction include: the reaction temperature is -20°C to 20°C, preferably -10°C to 0°C; the reaction time is 8-72h, preferably 12-18h.

[0039] The second aspect of the present invention provides polyimide-modified COFs prepared by the above-mentioned preparation method.

[0040] The third aspect of the present invention provides a polyimide-modified COFs film, wherein the polyimide-modified COFs film is obtained by film-forming the aforementioned polyimide-modified COFs.

[0041] The polyimide modified COFs membrane of the present invention can exist stably without cracks, and can be used for gas separation.

[0042] In the present invention, the specific method of the film forming process can be a common film forming process method in the art, such as a casting method, a printing method, etc. In a particularly preferred embodiment, the polyimide-modified COFs is dissolved in a solution containing polyimide, and the casting solution is configured using the principle of like dissolves like. After vacuum degassing, it is evenly coated on a glass plate, and dried in a 60°C blast oven for 12 hours to remove a large amount of solvent. The glass plate with the polyimide-modified COFs film is then placed in a 120°C vacuum oven and dried for 8 hours to remove trace solvents, cooled to 25°C, and the glass plate with the polyimide-modified COFs film is immersed in deionized water to make the polyimide-modified COFs film fall off. The fallen film is placed in a 60°C blast oven and dried for 12 hours. The film is then placed in a 120°C vacuum oven and dried for 8 hours to obtain a dry polyimide-modified COFs film.

[0043] In a particularly preferred embodiment, the weight ratio of the polyimide-modified COFs to the polyimide in the polyimide solution is 0.05-1.2:1, preferably 0.2-1:1.

[0044] In a particularly preferred embodiment, the solid content of the casting solution is 5wt%-50wt%, preferably 10wt%-30wt%.

[0045] According to the present invention, the thickness of the polyimide-modified COFs is 15-30 μm, preferably 18-20 μm.

[0046] A fourth aspect of the present invention provides an application of the aforementioned polyimide modified COFs membrane in the field of gas separation.

[0047] The present invention will be described in detail below through examples.

[0048] Testing method for polyimide modified COFs film and film thickness: Use the spiral micrometer method to directly measure 10 different positions of the film and take the average value.

[0049] Test method for gas permeability coefficient: using the differential pressure method, refer to the standards ISO 15105-1 and GB / T1038-2000, place the pre-treated membrane sample between the upper and lower test chambers and clamp them. First, vacuum the low-pressure chamber, then evacuate the entire system. When the vacuum degree is 4.9×10 -2psi, close the lower test chamber, fill the high-pressure chamber with 117psi of the test gas, and ensure that a constant pressure difference (adjustable) is formed on both sides of the sample; the test component gas permeates from the high-pressure side to the low-pressure side under the action of the pressure gradient. By monitoring the pressure inside the low-pressure side, the pressure-time curve of the permeation side is obtained. According to the obtained pressure-time curve, the area and thickness of the sample, data fitting is performed to obtain the permeability coefficient P of the material to the component gas. i ;

[0050]

[0051] V is the total volume of the low-pressure side, L is the membrane thickness, A is the membrane area, R is the ideal gas constant, T is the temperature, p2 is the pressure on the high-pressure side, p1 is the pressure on the low-pressure side, is the slope of the pressure in the steady-state permeate zone over time.

[0052] CO2 / N2 separation selectivity: The ratio of the permeability coefficients of CO2 / N2 when they pass through the membrane in single component form, dimensionless; the calculation formula is as follows:

[0053]

[0054] n-Butanol (BuOH), o-dichlorobenzene (o-DCB), 1,3,5-tri(4-aminophenyl)benzene (TPB), 2,5-bis(2-methoxyethoxy)terephthalaldehyde (BMTP), acetic acid, tetrahydrofuran, N-methylpyrrolidone (NMP), 4,4'-diaminodiphenyl ether, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, acetic anhydride, and pyridine are all commercially available.

[0055] Example 1

[0056] S1: Preparation of COFs powder:

[0057] 20 mL of n-butanol (BuOH), 20 mL of o-dichlorobenzene (o-DCB), 3.2 mmol of 1,3,5-tris(4-aminophenyl)benzene (TPB) and 4.8 mmol of 2,5-bis(2-methoxyethoxy)terephthalaldehyde (BMTP) were added to a 500 mL ampoule tube, ultrasonicated for 5 min, and then 4 mL of 6 mol / L acetic acid aqueous solution was added; the ampoule tube was evacuated and placed in a constant temperature oven at 120°C, reacted at 120°C for 72 h, and after the reaction was completed, COFs powder was obtained by centrifugation, and then the powder was washed with tetrahydrofuran, repeated 3 times, and the solid powder was placed in a vacuum oven at 120°C and dried for 12 h to obtain dry COFs powder.

[0058] S2: Preparation of polyimide modified COFs:

[0059] 1.2 g of COFs powder was ultrasonically dispersed in 110 mL of N-methylpyrrolidone (NMP), and the mass volume concentration of COFs powder in NMP was 0.01 g / mL; the solution was transferred to a three-necked flask, and 8 g (40 mmol) of 4,4'-diaminodiphenyl ether (ODA) was added under nitrogen protection, and stirred until ODA was completely dissolved, and then 12.4 g (40 mmol) of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) was added, wherein the weight ratio of COFs powder, diamine monomer and dianhydride monomer was 0.1:0.65:1, and polymerization reaction was carried out. The reaction temperature was 0°C and the reaction time was 14h. Then 13.5mL of acetic anhydride and 11.6mL of pyridine (including 144mmol of acetic anhydride and 144mmol of pyridine, and the molar ratio of acetic anhydride to pyridine was 1:1) were added, wherein the molar ratio of acetic anhydride in the mixed solution of diamine monomer and acetic anhydride and pyridine was 1:3.6. Dehydration was carried out at a temperature of 20°C and a time of 24h. The dehydrated solution was poured into excess deionized water, filtered and boiled at 60°C. The reaction was repeated 3 times to obtain polyimide-modified COFs, which were marked as PI-COFs-1#.

[0060] The electron microscope image of PI-COFs-1# is as follows Figure 1 As shown, in Figure 1 It can be seen that there are granular protrusions, forming a wrinkled surface, which is different from the smooth and continuous surface when only COFs exist; the XRD spectrum of PI-COFs-1# is shown in Figure 2 As shown, in Figure 2 There is a sharp peak in the sample, which proves that the substance has a high purity and the modification is relatively complete.

[0061] S3: Preparation of polyimide modified COFs membrane:

[0062] 50 mmol of ODA was added to 120 mL of NMP, and the mixture was stirred until the ODA was completely dissolved. Then, 50 mmol of ODPA was added to carry out polymerization reaction. The reaction temperature was 0°C and the reaction time was 10 h. Then, a mixed solution of 16.9 mL of acetic anhydride and 14.5 mL of pyridine was added (the mixed solution of acetic anhydride and pyridine included 180 mmol of acetic anhydride and 180 mmol of pyridine, and the molar ratio of acetic anhydride to pyridine was 1:1), wherein the molar ratio of the diamine monomer to the acetic anhydride in the mixed solution of acetic anhydride and pyridine was 1:3.6. The mixture was dehydrated at a temperature of 20°C and a time of 24 h. The dehydrated solution was poured into excess deionized water, filtered, and boiled at 60°C. The reaction was repeated 3 times to obtain polyimide, which was marked as PI-1#.

[0063] 1 g of the above PI-1# was dissolved in 18 g of NMP solution, 1 g of PI-COFs-1# was added thereto, stirred at 60°C for 24 h, and then ultrasonically dispersed for 1 h to prepare a casting liquid-1, wherein the solid content of the casting liquid-1 was 10 wt %; in the casting liquid-1, the weight ratio of PI-COFs-1# to the polyimide in the casting liquid-1 was 1:1, the casting liquid-1 was cooled to 25°C, vacuum degassed, and evenly coated on a glass plate, and dried in a 60°C forced air oven. , dry for 12 hours, then place the glass plate with the polyimide-modified COFs film in a vacuum oven at 120°C, dry for 8 hours, cool to 25°C, soak the glass plate with the polyimide-modified COFs film in deionized water to make the polyimide-modified COFs film fall off, place the film in a 60°C forced air oven, dry for 12 hours, then place the film in a vacuum oven at 120°C, dry for 8 hours, and obtain a dry polyimide-modified COFs film, marked as PI-COFs-1#MMM-1.

[0064] Example 2

[0065] S1: Prepare COFs powder according to the method of Example 1.

[0066] S2: Preparation of polyimide modified COFs:

[0067] 1 g of COFs powder was ultrasonically dispersed in 40 mL of N-methylpyrrolidone (NMP), and the mass volume concentration of COFs powder in NMP was 0.025 g / mL; the solution was transferred to a three-necked flask, and 1.6 g (7.8 mmol) of 4,4'-diaminodiphenyl ether (ODA) was added under nitrogen protection, and after stirring until ODA was completely dissolved, 2.4 g (7.8 mmol) of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) was added, wherein the weight ratio of COFs powder, diamine monomer and dianhydride monomer was 0.41:0.65:1, and polymerization was carried out. The reaction was carried out at a temperature of 0°C and a reaction time of 14 h, and then 2.66 mL of acetic anhydride and 2.2 mL of pyridine (including 28 mmol of acetic anhydride and 28 mmol of pyridine, and the molar ratio of acetic anhydride to pyridine was 1:1) were added, wherein the molar ratio of acetic anhydride in the mixed solution of diamine monomer and acetic anhydride and pyridine was 1:3.6, and dehydration was carried out at a temperature of 20°C and a dehydration time of 24 h. The dehydrated solution was poured into excess deionized water, filtered, and boiled at 60°C. The reaction was repeated 3 times to obtain polyimide-modified COFs, which were marked as PI-COFs-2#.

[0068] S3: Preparation of polyimide modified COFs membrane:

[0069] According to the method of Example 1, PI-1# was prepared.

[0070] 1 g of the above PI-1# was dissolved in 18 g of NMP solution, 1 g of PI-COFs-2# was added thereto, stirred at 60°C for 24 h, and then ultrasonically dispersed for 1 h to prepare a casting liquid-2, wherein the solid content of the casting liquid-2 was 10 wt %; in the casting liquid-2, the weight ratio of PI-COFs-2# to the polyimide in the casting liquid-2 was 1:1, the casting liquid-2 was cooled to 25°C, vacuum degassed, and evenly coated on a glass plate, and dried in a 60°C forced air oven. , dry for 12 hours, then place the glass plate with the polyimide-modified COFs film in a vacuum oven at 120°C, dry for 8 hours, cool to 25°C, soak the glass plate with the polyimide-modified COFs film in deionized water to make the polyimide-modified COFs film fall off, place the film in a 0°C blast oven, dry for 12 hours, then place the film in a vacuum oven at 120°C, dry for 8 hours, and obtain a dry polyimide-modified COFs film, marked as PI-COFs-2#MMM-1.

[0071] Example 3

[0072] S1: Prepare COFs powder according to the method of Example 1.

[0073] S2: Preparation of polyimide modified COFs:

[0074] 1 g of COFs powder was ultrasonically dispersed in 20 mL of N-methylpyrrolidone (NMP), and the mass volume concentration of COFs powder in NMP was 0.05 g / mL; the solution was transferred to a three-necked flask, and 0.1 g (0.5 mmol) of 4,4'-diaminodiphenyl ether (ODA) was added under nitrogen protection, and after stirring until ODA was completely dissolved, 0.15 g (0.5 mmol) of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) was added, wherein the weight ratio of COFs powder, diamine monomer and dianhydride monomer was 6.4:0.65:1, and polymerization reaction was carried out. The reaction temperature was 0°C and the reaction time was 14h. Then 0.23mL of acetic anhydride and 0.19mL of pyridine (including 2.4mmol of acetic anhydride and 2.4mmol of pyridine, and the molar ratio of acetic anhydride to pyridine was 1:1) were added, wherein the molar ratio of acetic anhydride in the mixed solution of diamine monomer and acetic anhydride and pyridine was 1:4.8. Dehydration was carried out at a temperature of 20°C and a time of 24h. The dehydrated solution was poured into excess deionized water, filtered, boiled at 60°C, and repeated 3 times to obtain polyimide-modified COFs, which were marked as PI-COFs-3#.

[0075] S3: Preparation of polyimide modified COFs membrane:

[0076] According to the method of Example 1, PI-1# was prepared.

[0077] 1 g of the above PI-1# was dissolved in 18 g of NMP solution, 1 g of PI-COFs-3# was added thereto, stirred at 60°C for 24 h, and then ultrasonically dispersed for 1 h to prepare casting liquid-3, wherein the solid content of casting liquid-3 was 10 wt%; in casting liquid-1, the weight ratio of PI-COFs-3# to the polyimide in casting liquid-3 was 1:1, casting liquid-3 was cooled to 25°C, vacuum degassed, and evenly coated on a glass plate, and dried in a 60°C forced air oven. , dry for 12 hours, then place the glass plate with the polyimide-modified COFs film in a vacuum oven at 120°C, dry for 8 hours, cool to 25°C, soak the glass plate with the polyimide-modified COFs film in deionized water to make the polyimide-modified COFs film fall off, place the film in a 60°C forced air oven, dry for 12 hours, then place the film in a vacuum oven at 120°C, dry for 8 hours, and obtain a dry polyimide-modified COFs film, marked as PI-COFs-3#MMM-1.

[0078] Example 4

[0079] S1: Prepare COFs powder according to the method of Example 2.

[0080] S2: Prepare polyimide-modified COFs according to the method of Example 2.

[0081] S3: Preparation of polyimide modified COFs membrane:

[0082] According to the method of Example 1, PI-1# was prepared.

[0083] 1 g of the above PI-1# was dissolved in 8 g of NMP solution, 1 g of PI-COFs-2# was added thereto, stirred at 60°C for 24 h, and then ultrasonically dispersed for 1 h to prepare casting liquid-4, the solid content of casting liquid-4 was 20 wt%; in casting liquid-4, the weight ratio of PI-COFs-2# to the polyimide in casting liquid-4 was 1:1, the casting liquid-4 was cooled to 25°C, vacuum degassed, and evenly coated on a glass plate, and placed in a 60°C blast oven. After drying for 12 hours, the glass plate with the polyimide-modified COFs film was placed in a vacuum oven at 120°C and dried for 8 hours. The glass plate was cooled to 25°C and immersed in deionized water to make the polyimide-modified COFs film fall off. The film was placed in a 60°C forced air oven and dried for 12 hours. The film was then placed in a vacuum oven at 120°C and dried for 8 hours to obtain a dry polyimide-modified COFs film, which was marked as PI-COFs-2#MMM-2.

[0084] Example 5

[0085] S1: Prepare COFs powder according to the method of Example 2.

[0086] S2: Prepare polyimide-modified COFs according to the method of Example 2.

[0087] S3: Preparation of polyimide modified COFs membrane:

[0088] According to the method of Example 1, PI-1# was prepared.

[0089] 0.95 g of the above PI-1# was dissolved in 9 g of NMP solution, 0.05 g of PI-COFs-2# was added thereto, stirred at 60°C for 24 h, and then ultrasonically dispersed for 1 h to prepare a casting liquid-5, wherein the solid content of the casting liquid-5 was 10 wt %; in the casting liquid-5, the weight ratio of PI-COFs-2# to the polyimide in the casting liquid-5 was 1:19, the casting liquid-5 was cooled to 25°C, vacuum degassed, and evenly coated on a glass plate, and blown at 60°C. The film was placed in a 60°C forced air oven and dried for 12 hours. The film was then placed in a 120°C vacuum oven and dried for 8 hours. The film was cooled to 25°C and immersed in deionized water to make the polyimide-modified COFs film fall off. The film was placed in a 60°C forced air oven and dried for 12 hours. The film was then placed in a 120°C vacuum oven and dried for 8 hours to obtain a dry polyimide-modified COFs film, which was marked as PI-COFs-2#MMM-3.

[0090] Example 6

[0091] S1: Prepare COFs powder according to the method of Example 2.

[0092] S2: Prepare polyimide-modified COFs according to the method of Example 2.

[0093] S3: Preparation of polyimide modified COFs membrane:

[0094] According to the method of Example 1, PI-1# was prepared.

[0095] 0.8 g of the above PI-1# was dissolved in 9 g of NMP solution, 0.2 g of PI-COFs-2# was added thereto, stirred at 60°C for 24 h, and then ultrasonically dispersed for 1 h to prepare a casting liquid-6, wherein the solid content of the casting liquid-6 was 10 wt %; in the casting liquid-6, the weight ratio of PI-COFs-2# to the polyimide in the casting liquid-6 was 0.25:1, the casting liquid-6 was cooled to 25°C, vacuum degassed, and evenly coated on a glass plate, and blown at 60°C. The film was placed in a 60°C forced air oven and dried for 12 hours. The film was then placed in a 120°C vacuum oven and dried for 8 hours. The film was cooled to 25°C and immersed in deionized water to make the polyimide-modified COFs film fall off. The film was placed in a 60°C forced air oven and dried for 12 hours. The film was then placed in a 120°C vacuum oven and dried for 8 hours to obtain a dry polyimide-modified COFs film, which was marked as PI-COFs-2#MMM-4.

[0096] Example 7

[0097] The method of Example 1 was followed, except that “13.45 g (40 mmol) of 2,2-bis(trifluoromethyl)-4,4-diaminophenyl ether (6FODA), stirred until 6FODA was completely dissolved, and then 12.4 g (40 mmol) of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) was added, wherein the weight ratio of COFs powder, diamine monomer and dianhydride monomer was 0.1:1.08:1” was used to replace “40 mmol of 4,4'-diaminodiphenyl ether (ODA), stirred until ODA was completely dissolved, and then 40 mmol of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) was added, wherein the weight ratio of COFs powder, diamine monomer and dianhydride monomer was 0.1:0.65:1” to obtain a dry polyimide modified COFs film, marked as PI-COFs-7#MMM-1.

[0098] Example 8

[0099] The method of Example 1 was followed, except that “40 mmol of 4,4'-diaminodiphenyl ether (ODA), stirred until ODA was completely dissolved, and then 50 mmol of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) was added, wherein the weight ratio of COFs powder, diamine monomer and dianhydride monomer was 0.08:0.52:1” was used to replace “40 mmol of 4,4'-diaminodiphenyl ether (ODA), stirred until ODA was completely dissolved, and then 40 mmol of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) was added, wherein the weight ratio of COFs powder, diamine monomer and dianhydride monomer was 0.1:0.65:1” to obtain a dry polyimide modified COFs film, marked as PI-COFs-8#MMM-1.

[0100] Example 9

[0101] The method of Example 1 is followed, except that “carrying out a polymerization reaction at a reaction temperature of 10°C and a reaction time of 24 hours” is used instead of “carrying out a polymerization reaction at a reaction temperature of 0°C and a reaction time of 14 hours,” to obtain a dry polyimide modified COFs film, which is marked as PI-COFs-9#MMM-1.

[0102] Comparative Example 1

[0103] S1: Prepare COFs powder according to the method of Example 1.

[0104] S2 is not performed.

[0105] S3: Prepare a COFs film in the manner of Example 1 to obtain a dry film, labeled COFs-MMM-D.

[0106] Comparative Example 2

[0107] S1 is not performed.

[0108] S2 is not performed.

[0109] S3: Preparation of membrane:

[0110] According to the method of Example 1, PI-1# was prepared.

[0111] Take 2g of the above PI-1# and dissolve it in 18g of NMP solution at 60°C for 24h to prepare a casting liquid-D2. The casting liquid-D2 is cooled to 25°C, vacuum degassed, and evenly coated on a glass plate. Dry it in a 60°C blast oven for 12h, then place the glass plate with the film in a 120°C vacuum oven, dry it for 8h, cool it to 25°C, soak the glass plate with the film in deionized water to make the film fall off, place the film in a 60°C blast oven, dry it for 12h, then place the film in a 120°C vacuum oven, dry it for 8h, and obtain a dry film, marked as PI-MMM-D.

[0112] The performance of each polyimide-modified COFs membrane prepared in Examples 1-9 and the membrane prepared in Comparative Examples 1-2 was tested, and the structures are shown in Table 1.

[0113] Table 1

[0114] Thickness(μm) <![CDATA[CO2 Permeability Coefficient (Barrer)]]> <![CDATA[Separation selectivity of CO2 / N2]]> Example 1 20 128 35 Example 2 18 108 50 Example 3 20 105 45 Example 4 16 115 40 Example 5 19 130 32 Example 6 21 102 55 Example 7 25 98 40 Example 8 30 110 43 Example 9 15 106 39 Comparative Example 1 20 25 2.3 Comparative Example 2 22 17 10.4

[0115] It can be seen from the results in Table 1 that the polyimide-modified COFs membranes in Examples 1-9 of the present invention can simultaneously have a high CO2 permeability coefficient and a CO2 / N2 separation selectivity.

[0116] By comparing Example 1 with Comparative Example 1, it can be seen that without polyimide modification, COFs are only prepared into membranes, which cannot be used for gas selective separation; by comparing Example 1 with Comparative Example 2, it can be seen that the membrane prepared only by polyimide has a small permeability coefficient and poor CO2 / N2 separation selectivity.

[0117] By comparing Example 1 with Example 7, it can be seen that the types of specific diamine monomers and dianhydride monomers can further affect the CO2 permeability coefficient and CO2 / N2 separation selectivity of the polyimide-modified COFs membrane.

[0118] By comparing Example 1 with Example 8, it can be seen that the specific amount of diamine monomer and dianhydride monomer can further affect the CO2 permeability coefficient and CO2 / N2 separation selectivity of the polyimide modified COFs membrane; the separation selectivity of Example 8 is good, but the permeability coefficient is greatly reduced.

[0119] By comparing Example 1 with Example 9, it can be seen that specific polymerization conditions can further affect the CO2 permeability coefficient and CO2 / N2 separation selectivity of the polyimide-modified COFs membrane; the separation selectivity of Example 9 is high, but the permeability coefficient is greatly reduced.

[0120] After being soaked in acid / base or heated, the polyimide-modified COFs membranes prepared in Examples 1-9 and the membranes prepared in Comparative Examples 1-2 can still be used for gas separation, which can prove that they have good stability.

[0121] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing polyimide-modified COFs, characterized in that: The preparation method comprises the following steps: S1: Preparation of COFs powder; S2: subjecting the COFs powder, diamine monomer and dianhydride monomer to a polymerization reaction to obtain polyimide-modified COFs.

2. The preparation method according to claim 1, wherein In S2, the diamine monomer is selected from At least one of, preferably selected from At least one of 3. The preparation method according to claim 1, wherein In S2, the dianhydride monomer is selected from At least one of and / or More preferably 4. The preparation method according to claim 1 or 2, wherein: In S2, the weight ratio of the COFs powder, the diamine monomer and the dianhydride monomer is 0.01-10:0.5-1.2:1, preferably 0.1-5:0.6-1.1:

1.

5. The preparation method according to any one of claims 1 to 4, wherein: In S2, the polymerization reaction is carried out in a solution; Preferably, the solvent contained in the solution is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide, preferably N-methylpyrrolidone; Preferably, the mass volume concentration of the COFs powder in the solvent is 0.005-0.1 g / mL, preferably 0.01-0.05 g / mL.

6. The preparation method according to any one of claims 1 to 5, wherein: In S2, the conditions of the polymerization reaction include: the reaction temperature is -20°C to 20°C, preferably -10°C to 0°C; the reaction time is 8-72h, preferably 12-18h.

7. A polyimide-modified COFs prepared by the preparation method according to any one of claims 1 to 6.

8. A polyimide modified COFs film, characterized in that: The polyimide-modified COFs film is obtained by film-forming the polyimide-modified COFs described in claim 7.

9. The polyimide-modified COFs film according to claim 8, wherein: The thickness of the polyimide modified COFs film is 15-30 μm, preferably 18-20 μm.

10. Use of the polyimide modified COFs membrane according to claim 8 or 9 in the field of gas separation.

Citation Information

Cited By

  • High-crystallinity polyimide covalent organic framework material with regular nanostructure as well as preparation method and application of high-crystallinity polyimide covalent organic framework material

    CN122325750A